KONDISI PSIKOLOGIS REMAJA PUTRI SAAT MENSTRUASI DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Erna Fitriatun; Sri Erny Muliyani; Sukarman (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study investigates the psychological conditions of adolescent girls during menstruation and their impact on participation in physical education lessons. The study involved 30 female students from grade XI at SMAN 2 Praya, selected through purposive sampling. A quantitative descriptive method was used, with a Likert-scale questionnaire (1–5) that measured psychological aspects such as mood changes, stress, and motivation during menstruation. The questionnaire showed strong validity (r-count ≥ 0.361) and high reliability, with Cronbach’s Alpha values of 0.863 for psychological conditions and 0.854 for menstrual phase. The results were analyzed using paired sample t-test and Cohen’s d to measure effect size. The t-test produced a t-count = 3.888, which was greater than the t-table value of 2.110 (p = 0.001), indicating a significant relationship between psychological conditions and participation in physical education. The effect size (Cohen’s d = 1.35) indicated a large practical significance of the relationship. The findings show that emotional fluctuations, stress, and fatigue during menstruation can reduce students' motivation and engagement in physical activities. Physical education teachers are recommended to implement adaptive teaching strategies that consider the psychological well-being of students during menstruation, including offering lighter physical activities and providing emotional support.